Effect of Different Concentrations of Gibberellic Acid on Seed Germination Behaviour and Seedling Vigour Index of Betula Utilis D. Don - Pitamber Singh Negi; Sandeep Sharma (Annals of Arid Zone, 2025)
A germination trial was conducted to study the effect of different concentrations of Gibberellic acid (GA3) on seed germination behaviour and seedling vigour of Betula utilis under Laboratory condition. The seeds collected from Barda Forest in Baspa Valley of Kinnaur district, Himachal Pradesh were treated with six different concentrations of Gibberellic Acid (GA3) viz., GA3 50ppm, GA3 100ppm, GA3 200ppm GA3 300ppm, GA3 400ppm and GA3 500ppm and control to study their effect on germination behaviour and seedling vigour index. Significant differences were observed in various germination parameters, seedling length and seedling vigour index of seeds treated with different pre-sowing treatments. The maximum germination per cent (79%), mean daily germination (3.76%), germination value (5.79), germination speed (9.07), seedling length (3.77cm) and seedling vigour index (297.83) were recorded in seeds treated with GA3 100ppm whereas maximum peak value (1.58) was recorded in seeds treated with GA3 400ppm and maximum germination energy (38.00) was recorded in seeds treated with GA3 500ppm. The minimum germination per cent (61.33%), mean daily germination (2.92%) and germination speed (7.07) were recorded in seeds treated with GA3 500ppm whereas minimum peak value (1.26), germination value (3.78), seedling length (2.25cm) and seedling vigour index (143.35) was recorded in seeds which were not given any pre-sowing treatment and minimum germination speed (7.07) was recorded in seeds treated with GA3 500ppm. The present investigation revealed that seeds of B. utilis possess embryo dormancy. Hence, seeds should be treated with GA3 100ppm before sowing in the nursery for better germination and seedling growth.